Refiguring Techniques in Digital Visual Research - Gómez Cruz, Edgar; Sumartojo, Shanti; Pink, Sarah (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book interrogates how new digital-visual techniques and technologies are being used in emergent configurations of research and intervention. It discusses technological change and technological possibility; theoretical shifts toward processual paradigms; and a respectful ethics of responsibility. The contributors explore how new and evolving digital-visual technologies and techniques have been utilized in the development of research, and reflect on how such theory and practice might advance what is "knowable" in a world of smartphones, drones, and 360-degree cameras. .
Keywords: Social sciences.; Research -- Moral and ethical aspects.; Ethnography.; Sociology -- Research.; elektronické knihy; electronic books